Sex hormones correlate with heart rate variability in healthy women and this correlation is conserved in women with well-controlled type 2 diabetes mellitus - Adriana Robles-Cabrera; Claudia Lerma; Silvia Ruiz-Velasco Acosta; Iván Pérez-Díaz; Ruben Fossion (PLoS ONE, 2025)
The autonomic nervous system and the endocrine system regulate cardiovascular physiology, and their alterations, as occurs in type 2 diabetes mellitus, are related to the development of cardiovascular complications. Sex hormones are major regulators of both cardiovascular and nervous tissue, and during postmenopause, the lack in hormone production can increase the risk for cardiovascular and autonomic diseases, even more in metabolic impairment such as in T2DM However, the evidence regarding whether sex hormones are related to autonomic activity is inconclusive. The goal of this paper was to evaluate the correlation between sex hormones and cardiac autonomic activity, as assessed by heart rate variability (HRV), women with well-controlled type 2 diabetes (T2DM) and healthy women as the control group. Subjects and methods In this study, four groups of women were designated according to their health status (control or T2DM) and fertility status (premenopausal or postmenopausal). Five serum sex hormones were measured (estradiol, progesterone, testosterone, LH and FSH), and time-domain and frequency-domain HRV indices were determined during three conditions: supine position, active standing, and rhythmic breathing. For the complete sample (n=118), bivariate Pearson correlations and linear multiple regressions were used to analyze the relationship between sex hormones, HRV indices, and other independent variables, such as glycemia and age. A p-value <0.05 was considered as significant. Results There were no differences in sex hormones or HRV indices when comparing the healthy and T2DM groups. All bivariate Pearson correlations were significant between sex hormones and HRV indices; estradiol, progesterone, and testosterone have positive correlations; meanwhile, LH and FSH were negative in the time-domain (SDNN, RMSSD, pNN20) and frequency domain (PLF and PHF) indices. Regression models adjusted for mean heartbeat intervals confirmed an association between all sex hormones and HRV indices. Estradiol maintained significance in the regression models for specific HRV indices during supine and active standing conditions even after adjusting for age and glucose levels. Conclusions All sex hormones correlate with HRV indices. Regression analysis confirms that this correlation is independent from the mean heartbeat interval. However, in regression models adjusted for age and glucose levels, only estradiol was found to be significant, and should be considered an important variable related to cardiovascular and autonomic balance in T2DM women and may provide crucial information to improve cardiovascular risk algorithms.